Human Periosteum Cell Osteogenic Differentiation Enhanced by Ionic Silicon Release from Porous Amorphous Silica Fibrous Scaffolds - ODATSU, Tetsurou (J Biomed Mater Res A, 2015)
Current synthetic grafts for bone defect filling in the sinus can support new bone formation but lack the ability to stimulate or enhance osteogenic healing. To promote such healing, osteoblast progenitors such as human periosteum cells must undergo osteogenic differentiation. In this study, we tested the hypothesis that degradation of porous amorphous silica fibrous (PASF) scaffolds can enhance human periosteum cell osteogenic differentiation. Two types of PASF were prepared and evaluated according to their densities (PASF99, PASF98) with 99% and 98% porosity, respectively. Silicon (Si) ions were observed to rapidly release from both scaffolds within 24 hours in vitro. PASF99 Si ion release rate was estimated to be nearly double that of PASF98 scaffolds. Mechanical tests revealed a lower compressive strength in PASF99 as compared to PASF98. Osteogenic expression analysis showed that PASF99 scaffolds enhanced the expression of activating transcription factor 4, alkaline phosphatase, and collagen (Col(I)α1, Col(I)α2). Scanning electron microscopy showed cellular and extracellular matrix ingress into both scaffolds within 16 days and the formation of Ca-P precipitates within 85 days. In conclusion, this study demonstrated that PASF scaffolds enhance human periosteum cell osteogenic differentiation by releasing ionic Si, and structurally supporting cellular and extracellular matrix ingress.